Ezetimibe and Cancer: Is There a Connection? - Gu, Jia; Zhu, Neng; Li, Hong-Fang; Zhang, Chan-Juan; Gong, Yong-Zhen; Liao, Duan-Fang; Qin, Li (Frontiers in Pharmacology, 2022)
The high level of serum cholesterol caused by the excessive absorption of cholesterol can lead to hypercholesteremia, thus promoting the occurrence and development of cancer. Ezetimibe is a drug that reduces cholesterol absorption and has been widely used for the treatment of patients with high circulating cholesterol levels for many years. Mechanistically, ezetimibe works by binding to NPC1L1, which is a key mediator of cholesterol absorption. Accumulating data from preclinical models have shown that ezetimibe alone could inhibit the development and progression of cancer through a variety of mechanisms, including anti-angiogenesis, stem cell suppression, anti-inflammation, immune enhancement and anti-proliferation. In the past decade, there has been heated discussion on whether ezetimibe combined with statins will increase the risk of cancer. At present, more and more evidence shows that ezetimibe does not increase the risk of cancers, which supports the role of ezetimibe in anti-cancer. In this review, we discussed the latest progress in the anti-cancer properties of ezetimibe and elucidated its underlying molecular mechanisms. Finally, we highlighted the potential of ezetimibe as a therapeutic agent in future cancer treatment and prevention.